Pendampingan Pengolahan Limbah Oli Sebagai Bahan Bakar Tambal Ban Motor Solusi Mengurangi Konsumsi Spritus Bagi Mekanik Di Desa Kangkung Ilir OKU Timur - Diana Novitasari (Jurnal Insan Pengabdian Indonesia, 2023)
The production of motorcycle vehicles has increased every year along with the increase in population and human needs. The impact of increasing vehicle production has led to an increase in waste oil as a byproduct. In order for the volume of waste oil to be reduced, human empowerment efforts are needed in utilizing and processing this waste to create valuable products. One of the steps that can be taken is to provide coaching and assistance to home mechanics in Kangkung Ilir Village. This assistance in processing waste oil to home mechanics has provided new knowledge for home mechanics on how to process waste oil into fuel. The fuel obtained from this assistance has proven effective in being used as fuel in the patching process of punctured motorcycle tires. The efficient use of spritus replacement fuel has a good ability as fuel, because in each patching process only 2 mL of fuel is needed, besides that it is able to provide service benefits for mechanics.